Comparison the effectiveness of Emotion-Focused Couple and Acceptance and Commitment Therapies on Marital Forgiveness in Incompatible Couples - Hossein Zaeimi; Ali Reza Rajaei; Mohammad Reza Saffaran Tousi; Hamid Nejat (Social Determinants of Health, 2023)
Background: Using effective interventions to reduce incompatibility among couples can play a role in preventing divorce in the family. The present study aimed to compare the effectiveness of emotion-focused couple therapy (EFCT) and acceptance and commitment therapy (ACT) on forgiveness in incompatible couples.